Using Health Applications in Blood Pressure Monitoring on Hypertension Control in Hypertension Patients: Literature Review - Kamalia, Annisa; Safitri, Destia; Aufa Suryana, Arriela; Sulastri, Afianti; Wahdini, Ridha; Salasa, Sehabudin; Sumartini, Sri (Jendela Nursing Journal (JNJ), 2025)
Background: hypertension is a leading risk factor for cardiovascular disease and remains a major public health challenge worldwide. Patient adherence to antihypertensive therapy is often suboptimal, particularly in low- and middle-income countries. Mobile health (mHealth) technologies have emerged as promising tools to enhance medication adherence and support self-monitoring of blood pressure. Objective: this review aims to evaluate the effectiveness of mHealth applications in improving blood pressure control among hypertensive patients. Methods: a systematic literature review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Relevant studies were identified through comprehensive searches of PubMed and Google Scholar using keywords such as “hypertension,” “telemedicine,” and “blood pressure.” Articles were screened based on predefined inclusion and exclusion criteria, and findings were synthesized descriptively to identify trends and outcomes across studies. Results: evidence indicates that mHealth applications integrating patient education, monitoring, and behavioral support are associated with improved medication adherence and reductions in blood pressure. However, results varied across studies due to differences in intervention design, duration of use, and patient characteristics. Conclusion: mHealth applications show potential as effective adjuncts to hypertension management, but further research is needed to optimize personalization, integration with health systems, and accessibility. Proper implementation of these technologies may enhance patient quality of life and contribute to reducing the global burden of cardiovascular disease.